Immunoprotective effect of virgin coconut oil against cyclophosphamide- induced hidtological changes in lymphoid tissues - Mohamad Mu'izuddin bin Senin (Kulliyah of Medicine, International Islamic University Malaysia, 2016)
Virgin coconut oil (VCO) is known for its health and therapeutic benefits mainly attributed to the polyphenols and medium chain fatty acid content. However, the immunomodulatory effects of VCO have not been extensively investigated. Therefore, in the present study, we examined the effects of VCO on cyclophosphamide (CY)-induced immunotoxicity of lymphoid tissues of Wistar rats. The animals were divided into seven groups consisting of six rats in each group. Group 1 served as the normal control while other groups were given CY of 10 mg/kg orally once daily for 4 weeks. Group 2 served as the negative control. Group 3A rats were treated with levamisole (LMS) for 4 weeks while Group 3B rats were given LMS for 6 weeks. Group 4A, 4B and 4C were administered with VCO at 5 mL/kg, 10 mL/kg and 15 mL/kg respectively for 6 weeks. The thymus, spleen and ileum sections were subjected to histological examination and immunohistochemical evaluation for T and B lymphocytes. Blood specimens were tested for full blood count, total protein, albumin, globulin, alanine aminotransferase, urea and creatinine. Histologically, the thymus, spleen and Peyer's patches (PP) of the ileum exhibited significant reduction in the lymphoid cellularity following daily administration of 10 mg/kg CY for 4 weeks. The thymus also showed a marked reduction in the medulla size with increased corticomedullary ratio. The white pulp areas of the spleen showed a reduction in the follicle number and size. The PP also showed diminished size of the lymphoid follicles and germinal centres. The spleen and PP revealed depletion of both T and B lymphocytes. Histological sections in the groups with VCO supplementation at 10 mL/kg and 15 mL/kg exhibited restoration of lymphoid cellularity and architecture. The total white cell counts, absolute lymphocyte counts and plasma globulin were significantly increased as compared to the group receiving only CY. This study revealed that VCO has protective effects on CY-induced histological changes in lymphoid tissues of Wistar rats.